Gas turbine engines ground vortex flows - Manquinho, Pedro Alexandre Rodrigues (2017)
When an aero-engine is operating near the ground at low aircraft speeds, high thrust and exposed to a crosswind the formation of a potent inlet ground vortex can arise. This structure create significant pressures losses and flow distortions and is swallowed by the engine. As a consequence, fan efficiency and thrust are severely affected and compressor surge may also occur. Inlet ground vortices are the cause of major foreign object damage (FOD) due to the ingestion of rocks, sand and other debris. The ingestion of foreign objects can cause notable damage to engine components as well as overall performance degradation. In the present work the flow fields for a full-scale aero-engine have been simulated for a range of ground clearances, engine diameters and intake velocity ratios under crosswind conditions. The aim of this study is to better understand the ground vortex inlet mechanisms supplying new information to foster vortex avoidance techniques. This work has shown large low pressure regions in front of the engine face for different engine-velocity/ratio-clearance distance combinations that extend to the ground especially where the vortex coalesces. There are two areas of no vortex as a function of h/Di and/∞ . The first is the anticipated frontier (threshold) between the regions vortex/no vortex, but a second one was detected for high values of /∞ (/∞ >50.00) that had not been mentioned in previous works. The inlet ground vortex mechanism is a very complex one which should be further investigated, and experimental works are desirable.